(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, on the basis of sources and scientific literature, the reasons and factors for the establishment of diplomatic relations between Amir Temur and the ruler of the Golden Horde are investigated. On the eve of the establishment of diplomatic, political and military relations between the two rulers, they discussed the political situation in the region and the goals of diplomatic relations.